Strategy for implementing digital marketing communication of unknown coffee through social media instagram - Muhammad Fathan; Budi Santosa (Jurnal Mantik, 2023)
Currently, the development of coffee shops has increased in popularity, resulting in market competition. Marketing communication strategy is a tool used by business people in promoting their products by making various innovations to achieve goals in the target market. The purpose of this research is to find out how the marketing communication implementation strategy used by Unknown coffee in using Instagram social media and what factors make unknown coffee's Instagram social media account active as a promotional medium. This research uses qualitative research methods with data collection methods through structured interviews. The population in this sample is the owner, 2 employees and 2 visitors of unknown coffee who have visited more than once and live in Surakarta. This research uses data analysis techniques in the form of qualitative content analysis.  The result of this research is that the digital marketing strategy carried out by Unknown coffee through an integrated marketing communication approach is carried out by combining several promotional mixes, such as advertising, social media and websites or internet marketing, sales promotion, public relations, personal selling, point of sale and merchandising, corporate identity, packaging, and word of mouth.